Rancang Bangun Ruteakost Sistem Informasi Rumah Kost Berbasis Web di Kota Medan - Justine Linia Harefa; Andy Paul Harianja (Yayasan Pendidikan Penelitian Pengabdian ALGERO, 2024)
The development of information technology has made various activities easier, including the search for temporary accommodations such as boarding houses. In Medan, many newcomers and local residents face difficulties finding boarding houses that meet their needs because the available information is often inaccurate or outdated. Additionally, boarding house owners encounter challenges in managing properties and finding tenants manually, which consumes a significant amount of time and effort. To address these issues, Ruteakost was developed as a web-based boarding house information system Waterfall method to ensure a structured and systematic approach. Ruteakost is designed to simplify the search for boarding houses based on facilities and strategic locations, while also helping property owners manage their properties without the need for direct interaction with potential tenants. The system offers features such as tenant management, rent payment, property maintenance, and financial reporting, aiming to create an efficient, transparent, and easy-to-monitor process. Furthermore, Ruteakost introduces integrated online payment options and a more user-friendly interface. This innovation aims to overcome common issues found in other platforms, such as outdated boarding house listings and complex interfaces that can confuse users. Through new, effective, and intuitive features, Ruteakost provides a reliable solution for property owners to improve their operational efficiency, while also offering a better search experience for prospective tenants. Thus, Ruteakost not only assists in the management and booking of boarding houses in Medan but also strives to enhance service quality through the integration of more advanced technology, focusing on user needs and easy access to information.